2014
DOI: 10.3109/0284186x.2014.925578
|View full text |Cite
|
Sign up to set email alerts
|

A treatment planning and delivery comparison of volumetric modulated arc therapy with or without flattening filter for gliomas, brain metastases, prostate, head/neck and early stage lung cancer

Abstract: It was generally possible to produce FFF-VMAT plans with the same target dose coverage and doses to organs at risk as STD-VMAT plans. Target dose homogeneity tended to be somewhat inferior for FFF-VMAT for the larger targets investigated. For stereotactic radiotherapy, FFF-VMAT resulted in a considerable time gain while maintaining similar plan quality compared to STD beams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 25 publications
8
37
0
Order By: Relevance
“…Furthermore, Alongi et al 17 did not include a systematic investigation into the optimal VMAT delivery technique. In this regard, we sought to compare 1-and 2-arc VMAT-FFFM deliveries, a method of delivery not investigated by Gasic et al 18 Ideally, the comparison should consider dosimetry (target volume coverage and doses to the OAR), treatment time, and the degree of the patient's intrafractional motion. Accordingly, the present planning study evaluated dosimetry and treatment time, whereas our upcoming clinical trial will investigate intrafractional motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Alongi et al 17 did not include a systematic investigation into the optimal VMAT delivery technique. In this regard, we sought to compare 1-and 2-arc VMAT-FFFM deliveries, a method of delivery not investigated by Gasic et al 18 Ideally, the comparison should consider dosimetry (target volume coverage and doses to the OAR), treatment time, and the degree of the patient's intrafractional motion. Accordingly, the present planning study evaluated dosimetry and treatment time, whereas our upcoming clinical trial will investigate intrafractional motion.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Only low-and intermediate-risk patients were considered in these studies. Furthermore, Alongi et al 17 did not include a systematic investigation into the optimal VMAT delivery technique.…”
Section: Discussionmentioning
confidence: 99%
“…With more and more widespread and profound application of linear accelerator in radiotherapy, particularly the appearance of flattening filter free (FFF) beams in recent years, several investigators have studied the role of FFF beams for SRS in brain metastases [1314]. The use of volumetric modulated arc therapy (VMAT) for SRS with FFF beams has recently been shown to shorten treatment time if compared with traditional flattening filter (FF) beams [1516].…”
Section: Introductionmentioning
confidence: 99%
“…1 These beam modes offer several advantages for SABR treatments including higher dose rate and smaller out of field scatter. 2,3 Treatment planning studies 4,5 have shown that comparable plan quality can be achieved with FFF beams compared with conventional flat beams, the primary benefit to the patient being significantly reduced beam-on time. However, most commercial treatment planning systems still struggle to provide accurate dosimetry for small field sizes and inhomogeneous media, which are both relevant concerns for SABR lung treatment.…”
Section: Introductionmentioning
confidence: 99%